Management Accounting of Design and Prepress Costs in the Printing Industry - Strotcen, Andrii (Herald of Economics, 2026)
In the modern creative economy and Industry 4.0, the printing industry is undergoing a structural transformation. Design and prepress are evolving from auxiliary stages to key elements of value creation. The digitalization of production shifts the complexity to intellectual and information operations, making traditional cost accounting approaches obsolete and causing a bottleneck effect. The article aims to substantiate methodological approaches to management accounting of design and prepress costs based on the integration of Activity-Based Costing (ABC), Management Information Systems (MIS), and the JDF standard, as well as to evaluate their impact on cost calculation accuracy and cost management efficiency. The study identifies the intangible and intellectual nature of design costs and highlights the limitations of traditional costing systems, which lead to cross-subsidization. The research proves that the integration of the ABC approach with MIS and JDF enables real-time data collection, eliminates cost distortions, and provides accurate cost allocation based on actual resource consumption. Empirical modeling demonstrates that traditional methods undervalue complex design projects, while the proposed integrated ABC approach increases pricing accuracy. The integration of ABC, MIS, and JDF ensures adequate reflection of design costs in the printing industry, transforming them from indirect expenses into a strategically manageable resource. Further research should focus on the practical implementation of these integrated systems in specific printing enterprises to optimize their strategic management and improve competitiveness in the digital economy.